Whole Brain Radiation-Induced Vascular Cognitive Impairment: Mechanisms and Implications - Warrington, Junie P. (J Vasc Res, 2013)
Mild cognitive impairment is a well-documented consequence of whole brain radiation therapy (WBRT) that affects 40-50% of long-term brain tumor survivors. The exact mechanisms for the decline in cognitive function post-WBRT remain elusive and no treatment or preventative measures are available for use in the clinic. Here, we review recent findings indicating how changes in the neurovascular unit may contribute to the impairments of learning and memory. In addition to affecting neuronal development, WBRT induces profound capillary rarefaction within the hippocampus-a region of the brain important for learning and memory. Therapeutic strategies such as hypoxia, which restore the capillary density, result in the rescue of cognitive function. In addition to decreasing vascular density, WBRT impairs vasculogenesis and/or angiogenesis, which may also contribute to radiation-induced cognitive decline. Further studies aimed at uncovering the specific mechanisms underlying these WBRT-induced changes in the cerebrovasculature are essential for developing therapies to mitigate the deleterious effects of WBRT on cognitive function.